A REVIEW ON DISSOLUTION APPARATUS - Sharma, Shobhit; Khinchi, M. P.; Agrawal, Dilip; Sharma, Natasha; Gupta, M. K. (Asian Journal of Pharmaceutical Research and Development, 2013)
For orally administered non-solution dosage forms, in vitro performance test procedure such as dissolution test is performed for various purposes. It is one of the routinely performed quality control tests for the oral solid dosage forms. Dissolution research started to develop about 100 years ago as a field of physical chemistry and since then important progress has been made. Apart from its importance in the field of pharmaceutical analysis it is also important in pharmaceutical formulation technology and drug discovery. In this review paper we will focus on different mathematical aspects of dissolution process and different dissolution apparatuses are in use. We will discuss some non-conventional dissolution testing methods. The review will also focus on modernization of dissolution process and dissolution testing apparatuses including automation in dissolution testing and adoption of fiber optic technology.